Development of a software and technical complex for a two-channel detecting system for continuous registration of X-ray and gamma radiation - Bochek, G.L.; Kapliy, O.A.; Karpus, S.H.; Kiprich, S.K.; Kovalenko, G.D.; Ovchinnik, V.D.; Semisalov, I.L.; Shirokopetlev, F.O.; Shlyakhov, I.M.; Shulika, M.Yu.; Vasiliev, G.P.; Yalovenko, V.I. (Problems of Atomic Science and Technology, 2023)
A compact spectrometric tract and software for work as part of a two-channel detecting system for continuous registration of X-ray and gamma radiation in a wide range of energies have been developed. The complex is designed to work with silicon planar uncooled detectors. The software allows you to process information from each spectrometric channel and provide information in the form of a integrated spectrum. The design of the detecting module, which combines low-energy and high-energy detectors in one housing has been developed. Розроблено малогабаритний спектрометричний тракт та програмне забезпечення для роботи у складі двоканальної детектуючої системи безперервної реєстрації рентгенівського та гамма-випромінювання у широкому інтервалі енергій. Комплекс розрахований на роботу з кремнієвими планарними неохолоджуваними детекторами. Програмне забезпечення дозволяє проводити обробку інформації від кожного спектрометричного каналу та подавати інформацію у вигляді єдиного спектра. Розроблено конструкцію детектуючого модуля, який об’єднує в одному корпусі низькоенергетичний і високоенергетичний детектори.